How primary and secondary appraisals of daily stressful events influence negative and positive affect - Fernández Castro, Jordi; Ferrer, Iris; Edo, Sílvia; Rovira, Tatiana (Anales de Psicología / Annals of Psychology, 2022)
The aim of this study was to evaluate the influence of primary and secondary appraisal, and of coping strategies, on daily stress, taking into account any possible effect of the big five personality traits. Over 10 days, a cohort of 122 people filled out an on-line diary in which they recorded the most important stressful event each day, their primary and secondary appraisal of this, and how they coped with it. The results indicate that negative affect is influenced by a high degree of primary appraisal, limited secondary appraisal and a high rate of refusal, with no significant influence of personality traits. Positive affect is mainly influenced by a lower extent of primary appraisal, more secondary appraisal, and by a low rate of refusal and of social support seeking. Moreover, a low level of neuroticism was a predictor of greater positive affect. These data are discussed, highlighting the importance of a situational assessment of stressful episodes at each moment to not only understand the effects of stress on health but also, to develop effective interventions.